CORRELATION OF KI67 LEVEL TO METASTATIC EVENTS IN NASOPHARYNGEAL CARCINOMA - Eriza; Kurnia, Ermalinda; Utama, Denny Satria (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction Nasopharyngeal carcinoma (KNF) is a malignant squamous cell tumor occurring in the nasopharyngeal epithelial region where the cuboid epithelium is transformed into squamous cells. One of the typical signs of malignancy is uncontrolled cell proliferation. K67 is an immunohistochemical (IHC) test to assess cell proliferation activity. Increased Ki67 expression is associated with increased mitotic activity in cell proliferation. Objective To determine the correlation of ki67 expression to regional and distant metastases events of nasopharyngeal carcinoma at KNF in Dr. Mohammad Hoesin Palembang. Methods This cross-sectional study was conducted on 31 subjects of KNF patients who had been diagnosed in Oncology Division of Department of Ear Nose and Throat Head Neck Surgery, then performed immunohistochemistry inspection of KI67 in Department of Anatomical Pathology of Dr. Mohammad Hoesin Palembang. The subjects were collected consecutive sampling from October to December 2017 and performed other tests for staging such as computer tomography, chest x ray and abdominal ultrasound. Results In the Ki67 level correlation analysis of the incidence of metastasis in nasopharyngeal carcinoma, the correlation coefficient was 0.98 with very strong correlation strength and the positive correlation was not statistically significant (p=0.599). However, in Ki67 level correlation analysis of histopathology result of nasopharyngeal carcinoma was found correlation coefficient of 0.385 and positive correlation which was statistically significant (p=0.032). Conclusion Ki67 levels of metastatic occurrence in nasopharyngeal carcinoma have no statistically significant correlation. However, Ki67 level on histopathological results of nasopharyngeal carcinoma and Ki67 immunoreactivity with primary tumor has a statistically significant correlation.